The Influence of Internal Control and Probity Audit on Fraud Prevention in Procurement of Goods and Services (Study at the Palopo City Inspectorate Office) - Tiara Madani. B; Andika Rusli; Sahrir (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the effect of internal control and probity audit on the prevention of fraud in the procurement of goods and services at the Palopo City Inspectorate office. This study uses a quantitative approach by distributing questionnaires to 31 auditors of the Palopo City Inspectorate office as respondents, who were selected through purposive sampling techniques . Data analysis was carried out using data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that internal control has a significant effect on the prevention of fraud in the procurement of goods and services and probity audit has a significant effect on the prevention of fraud in the procurement of goods and services. This study emphasizes the importance of strengthening internal control and probity audit in the supervision of goods and services as an effective effort to prevent fraud.